2003
DOI: 10.1108/01443570310506704
|View full text |Cite
|
Sign up to set email alerts
|

Kaizenin Japan: an empirical study

Abstract: This paper reports the study of kaizen as practised in a selection of Japanese companies. After discussing the general understanding of kaizen and proposing a clear definition, the paper describes the methodology of the study, and presents findings from the research, taking Nippon Steel Corporation (NSC) as a base model and comparing this with the data from other companies. The development of kaizen activity in NSC is presented together with a description of the current nature of kaizen, which is compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
240
1
23

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(285 citation statements)
references
References 27 publications
11
240
1
23
Order By: Relevance
“…(Dahlgaard, Kristensen, & Kanji, 2002) Small continuous changes for the better. (Brunet & New, 2003) Pervasive and continual activities, outside the contributor's explicit contractual roles, to identify and achieve outcomes he believes contribute to the organisational goals. (Boer & Gertsen, 2003) in (Middel, op de Weegh, & Gieskes, 2007) The planned, organised and systematic process of ongoing, incremental and company-wide change of existing practices aimed at improving company performance.…”
Section: Limitationsmentioning
confidence: 99%
“…(Dahlgaard, Kristensen, & Kanji, 2002) Small continuous changes for the better. (Brunet & New, 2003) Pervasive and continual activities, outside the contributor's explicit contractual roles, to identify and achieve outcomes he believes contribute to the organisational goals. (Boer & Gertsen, 2003) in (Middel, op de Weegh, & Gieskes, 2007) The planned, organised and systematic process of ongoing, incremental and company-wide change of existing practices aimed at improving company performance.…”
Section: Limitationsmentioning
confidence: 99%
“…Moreover, information systems are often seen as a precursor to innovation capability (Cepeda-Carrion et al 2012). Advice that builds capability is cumulative, requires persistence and delves more deeply within the firm (Brunet and New 2003). Done, Voss and Rytter (2011) in eight comparative case studies of the impact of a Manufacturing Advisory Service (MAS) intervention in the UK found only one of their companies persisted with the intervention beyond the lifetime of the external assistance; nevertheless, work on adopting management practices highlights ongoing benefits that persist (Ichniowski et al 1997, Bloom and Van Reenen 2007, Døving and Gooderham 2008.…”
Section: Advice That Builds Capabilities Versus Advice That Uses Extamentioning
confidence: 99%
“…It is seen as one of lean tools that help to ensure that operations become more smoothly by removing wasteful activities that are of no value from a customer perspective (Venkataiah and Sagi, 2012). According to Brunet et al (2003), almost the same that KE can help to avoid wastage by employees with a full sense of responsibility, punctuality and as a tool for improvement and change. Therefore, Table 1.0 below shows the factors from previous studies for implementing KE.…”
Section: Kaizen Event (Ke)mentioning
confidence: 99%
“…It is one of the manufacturing strategies in lean manufacturing or in Toyota Production System (TPS) (Anh et al, 2011). KE aims to control the operation of the working environment; it also aims to improve processes and efficiency of workers (Brunet et al, 2003;Ventakiah and Sagi, 2012). According Doolen et al, (2008) Kaizen is one of the mechanisms of structural improvement that could be implemented by any organization.…”
Section: Kaizen Event (Ke)mentioning
confidence: 99%